Immunology in the reproduction. First part - Pacheco, José (1996)
The main aspects of interaction between reproductive and immunologycal proceses are presented in this review. In this first part, we outline the knowledge of immune system general aspects, particularilly in humoral and cellular factors of the immune response the immunological reactivity during the pregnancy and the role of the placenta in this interaction are reviewed.